A Socio-economic Study on Pros & Cons of SRI Method of Paddy Cultivation In Ormanjhi Block of Ranchi District, Jharkhand - Punit Kumar Agarwal and Ajay Kumar, (Indian Journal of Extension Education, 2017)
Rice is a staple food for more than half of the world’s population. A major issue with the traditional system of paddyproduction, particularly green revolution technology is input intensive and favors cash rich farmers. Increasingprices of agricultural inputs prevent poor farmers from completely adopting modern production technologies.Under such circumstances the System of Rice Intensification (SRI) method was suitable and followed by thefarmers. System of rice intensification is a method for increasing the productivity of rice cultivation while at thesame time reducing inputs, including seeds and fertilizers, and water requirements. The present study was conductedin Hindebli, Kuchu, Tapa, Khulsi and Bundu villages of Ormanjhi block of Ranchi district. In this study the mainobjectives were to study the socio-economic profile of paddy growers, perception and constraints confronted bypaddy growers under SRI method of paddy cultivation. Study revealed that the major constraints in SRI productionwere lack of awareness, Scarcity of skilled labour, nursery management, and drudgery in cono-weeder uses. Themajor perception regarding SRI method of paddy cultivation were low demand of water, higher production or yield,remuneration from government, low seed requirement, low costs of input uses.